Shotwavemod: An Open Package For Acoustic 2D/3D Seismic Wavefield and Shot Acquisition Modeling Using the Pseudo Spectral Element and Finite Difference Methods - Abdullah, Agus; Pranowo, Waskito; Ahmad Zaky, Dicky (Indonesian Journal on Geoscience, 2025)
Shotwavemod is an open package for 2D/3D acoustic seismic wave simulation, using the Pseudo Spectral Element and Finite Difference Method. It can also be used for forward modeling of seismic reflection acquisition. The shotwavemod offers straightforward execution of the simulation process, yet customizable parameters. The algorithm was optimized using vectorization and parallel computation to speed up the computational time. The simulation results of the Pseudo Spectral Element Method was compared to the Finite Difference Method. It is observed that the Finite Difference Method resulted in ringing artifacts as a numerical dispersion, particularly for higher frequencies. Nevertheless, with higher computational cost, the Pseudo Spectral Element Method effectively handles this numerical dispersion issue. The shotwavemod was tested for a complex velocity model of the Marmousi. The results are quite promising, where shot gathers of seismic reflections are successfully established corresponding to the complex structure of the Marmousi. The shotwavemod is accessible to the public, and is a suitable tool for educational and research purposes involving seismic wave simulation.